The Role of Strategic Consciousness in Enhancing the Strategic Vigilance - Fadhil, Alaa Hussein; Hasan, Mohammed Faez; AL- Sammari, Ahmed Abdullah Amanah; Qandeel, Ahmed Muhammadridha Abdulrasool (The journal of contemporary issues in business and government, 2021)
The research aims to test the impact of strategic consciousnesson strengthening the strategic vigilance ininvestmentorganizations by analyzingresponses from124managers working for administrative, engineering and technical sectors inside Al-Kafeel Group for Public Investments in Karbala.We applied constructs of (Turkay et al., 2012) (forstrategic consciousness (Reframing, System thinking, Learning orientation and Reflection)and the model of(Fadhiela et al., 2018) for strategic vigilance (Technological vigilance, Competitive vigilance, Marketing vigilance, and Environmental Vigilance). The collected responses were analyzed using structural equation modelling to measure Cronbach’s alpha coefficient, confirmatory factor analysis, and Pearson’s correlation for the constructs and latent variables. Amanager’sstrategic consciousnessposed an active impact on enhancing the strategic vigilance of the firms. The research sample is in the context of competition in the Iraqi industrial and investing sectors. Strategic consciousnessis instrumental in improving the positive relationship in strategic vigilance in line with the customized prerequisites and the dynamic setting of workplaces. Implications on the provision of valuable production would add up to the targeted local self-sufficiency.